P-from wave velocities and anisotropy of typical rocks the Yunkai Mts. (Guangdong and Guangxi, China) and constraints on the composition of the crust beneath the South China Sea. (1st December 2016) - Ji, Shaocheng; Wang, Qian; Salisbury, Matthew H.; Wang, Yuejun; Jia, Dong
Graphical abstract: Highlights: 12 seismic transects from the South China Sea and its continental margins have been interpreted. The crust of the Cathaysia block has a mafic-to-felsic layer thickness ratio of 41–43%. High velocity lower crust beneath South China Sea could be formed by underplating of mafic magmas. Abstract: In order to provide constraints on the interpretation of seismic data of the crust beneath the South China Sea (SCS) and its continental margins, we have measured P-wave velocities and anisotropy as a function of hydrostatic confining pressure, up to 650 MPa, for 31 representative samples (i.e., granite, diorite, felsic gneiss, mylonite and ultramylonite, amphibolite, schist, and marble) from the Yunkai Mts (Guangdong and Guangxi Provinces, China) that represent the crystalline basement beneath the continental margins of the SCS. The intrinsic velocity of each crack-free rock increases with increasing density (ρ) which is linearly dependent on the chemical composition: ρ increases with increasing MgO, CaO, FeO + Fe2 O3, and Al2 O3 contents, but decreases with increasing contents of SiO2  and Na2 O + K2 O. Most of the rocks have small (<4%) or moderate (4–8%) seismic anisotropy because (1) the contribution of quartz to the bulk anisotropy opposes that of feldspar, and (2) the rocks only contain small amounts of amphibole and/or mica. The interpretation of 12 seismic transects suggests that the crust of the Cathaysia block (the southern part of South China) has a mafic-to-felsic layer thickness ratio (Rm/f ) of 41–43% and the ratio shows a general increase from the continental margin to the central basin. The high velocity (7.0–7.6 km/s) materials in the lower crust could be either the former lower crustal mafic rocks that were present before rifting, which have experienced less extensional thinning than the felsic upper crust, or the materials crystallized from mafic magma which underplated the lower crust from the partially molten upper mantle during rifting.